2002
DOI: 10.4049/jimmunol.169.8.4213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Marrow-Derived Stromal Cells in the Maintenance of Plasma Cell Longevity

Abstract: Protective circulating Abs originate primarily from long-lived plasma cells in the bone marrow. However, the molecular and cellular basis of plasma cell longevity is unknown. We investigated the capacity of primary bone marrow-derived stromal cells to maintain plasma cell viability in vitro. Plasma cells purified from the bone marrow or lymph nodes died rapidly when plated in media, but a subpopulation of plasma cells survived and secreted high levels of Ab for up to 4 wk when cocultured with stromal cells. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(113 citation statements)
references
References 58 publications
0
111
2
Order By: Relevance
“…For instance, the integrin α 4 β 1 (VLA-4) has been described as a key factor for the generation of long-lived PC [14,44]. Reports show that these cells rely on a combination of soluble and contact-mediated mechanisms to fulfill hematopoietic and immunomodulatory functions [4547].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the integrin α 4 β 1 (VLA-4) has been described as a key factor for the generation of long-lived PC [14,44]. Reports show that these cells rely on a combination of soluble and contact-mediated mechanisms to fulfill hematopoietic and immunomodulatory functions [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that there are functionally unique subpopulations of Ab-secreting cells (ASC) 3 present within mammals, including the plasmablast (7,8), the short-lived plasma cell (9,10), and the long-lived plasma cell (11)(12)(13)(14)(15). The plasmablast is an ASC that is distinguished from plasma cells by its ability to proliferate, its short half-life, and its low levels of CD138, B220, and presence of c-Myc (7, 16 -18).…”
mentioning
confidence: 99%
“…Increased integrin trans-regulation might also have utilities beyond tumor immunotherapy. Migration and survival of long-lived plasma cells in the bone marrow appears to be dependent on α4 and αLβ2 integrins (3135) and could involve integrin trans-regulation. Thus, enhanced integrin trans-regulation offers a new approach to selectively potentiate β2 integrin-mediated homing of lymphocytes and plasma cells.…”
Section: Resultsmentioning
confidence: 99%